2018
DOI: 10.1074/jbc.m117.815357
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct differences in prion-like seeding and aggregation between Tau protein variants provide mechanistic insights into tauopathies

Abstract: The accumulation of aberrantly aggregated microtubule-associated protein tau (MAPT) 1 defines a spectrum of tauopathies, including Alzheimer's disease. Mutations in the MAPT gene cause frontotemporal dementia with Parkinsonism linked to chromosome 17 (FTDP-17), characterized by neuronal pathological tau inclusions in the form of neurofibrillary tangles and Pick bodies, and in some cases glial tau pathology. Increasing evidence points to the importance of prion-like seeding as a mechanism for the pathological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(152 citation statements)
references
References 86 publications
9
139
0
Order By: Relevance
“…Notably, homotypic recruitment of P301S and P301L monomers onto their respective seeds was even more efficient (Ͼ90%) and faster (t1 ⁄ 2 ϭ 5-9 min) than heterotypic recruitment of htau40 ( Fig. S2), in agreement with previous studies that suggested preferential growth of mutant over WT Tau (12,(33)(34)(35). To obtain visual confirmation for the recruitment of WT Tau onto mutant seeds, we next collected TEM images of negatively stained samples ( Fig.…”
Section: P301s and P301l Induce Cross-seeding Barriersupporting
confidence: 86%
“…Notably, homotypic recruitment of P301S and P301L monomers onto their respective seeds was even more efficient (Ͼ90%) and faster (t1 ⁄ 2 ϭ 5-9 min) than heterotypic recruitment of htau40 ( Fig. S2), in agreement with previous studies that suggested preferential growth of mutant over WT Tau (12,(33)(34)(35). To obtain visual confirmation for the recruitment of WT Tau onto mutant seeds, we next collected TEM images of negatively stained samples ( Fig.…”
Section: P301s and P301l Induce Cross-seeding Barriersupporting
confidence: 86%
“…However, within the proposed mechanism of tau conformational-templating and seeding, the aggregation of tau monomer to tau seeds must first take place. A recent study from Strang et al, [55], indicates that specific regions within tau, play a key role in regulating aggregation and seeding. In particular, P301L and S320F tau mutants are uniquely able to aggregate with seeding when compared to WT tau, and aggregated P301L tau failed to sequester soluble WT tau into insoluble aggregates in HEK293 cells seeding model [55].…”
Section: "Prion-like" Misfolding Of A and Tau: Implication For Alzhementioning
confidence: 99%
“…A recent study from Strang et al, [55], indicates that specific regions within tau, play a key role in regulating aggregation and seeding. In particular, P301L and S320F tau mutants are uniquely able to aggregate with seeding when compared to WT tau, and aggregated P301L tau failed to sequester soluble WT tau into insoluble aggregates in HEK293 cells seeding model [55]. Moreover, because of a lower tendency of P301L tau to aggregate in the presence of WT tau expression, it is possible that WT tau may reduce template conformation of P301L tau.…”
Section: "Prion-like" Misfolding Of A and Tau: Implication For Alzhementioning
confidence: 99%
See 1 more Smart Citation
“…Organotypic BSCs were washed in PBS, fixed on their inserts with 4% paraformaldehyde for 1 h, and then stained with 0.0125% Thioflavin S as previously described [31]. In brief, a stock solution of 1% Thioflavin S (Sigma-Aldrich) in 50% EtOH in PBS was filtered through a 0.2-μm filter.…”
Section: Thioflavin S Stainingmentioning
confidence: 99%